Characterization of a Mouse Factor IX cDNA and Developmental Regulation of the Factor IX Gene Expression in Liver - Yao, Shou-Nan; DeSilva, Audrey H; Kurachi, Sumiko; Samuelson, Linda C; Kurachi, Kotoku (Thrombosis and Haemostasis, 1991)
A mouse factor IX cDNA was isolated and characterrzed. The cDNA was 1,837 bp in length and contained the coding region as well as short 5’ and 3’ untranslated sequences. Northern blot analysis of liver RNA showed two mRNA species of 3.2 kb (major) and 2.2 kb (minor) for the mouse factor IX. An antisgnse RNA probe prepared from the mouse cDNA was employed to determine the steady state level of factor IX mRNA in mouse liver at various developmental stages. The factor IX mRNA level was very low (2–5% of the adult level) during the gestational period until day –3 (gestational day 17) followed by a rapid increase at day –2 through birth. This phase of rapid increase was followed by a gradual increase before it reached the adult level at around 20 to 24 days. At birth, the factor IX mRNA level was found to be at about 43% of that of the adult. The rnRNA levels in mouse liver agreed well with the plasma factor IX activity levels. These results indicate that reduced factor IX activity in newborns is due to the low levels of factor IX mRNA available for translation.